1893 N.C. Sess. Laws 468–69, Pub. Laws, ch. 514, §§ 1-2 - (:unkn) unknown (General Publisher, 1893)
Prohibiting the transfer of any pistol, pistol cartridge, brass knucks, Bowie knife, dirk, loaded cane, or slingshot to a minor.
--
Keywords: TRANSFER - MINORS